Analisis Pengaruh Jumlah Tanggungan Keluarga, Umur, Pendidikan Dan Status Pekerjaan Terhadap Pendapatan Keluarga Wanita Single Parent - Umi Rahayu, Shabrina; Tisnawati, Ni Made (Jurnal Ekonomi Kuantitatif Terapan; 2014: Vol. 7, No. 2, Agustus 2014 (pp. 83-198), 2015)
Women have significant roles in development, such as women as human resources in development, women as a subject in development, and women as a family builder. This study focused on how women’s role as a family builder in a single parent status. The variables used in this study are number of dependents, age, education, and employment status to be analyzed its impact on income of single parent women. This research took a place in Sesetan Village, South Denpasar with the number of samples taken were 84 samples with the purposive sampling method. The data was collected by questionnaires and interviews. Multiple linear regression analysis with quantitative and qualitative independent variables was used as the analysis technique. Based on the analysis result had found that variables of number of dependents, age, education, and employment status had a positive impact as a partial to the income of single parent women. The government’s efforts for all the kinds of women coaching are important to be developed, with the aim to the community prosperity especially single parent women who have heavier burden of life. The attention of education, health, and economy is necessary to improved to ease the burden for the families of the single parent women.
Keywords: single parent women; number of dependents; age; education; employment status; income